z=90-4x+6y

Simple and best practice solution for z=90-4x+6y equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for z=90-4x+6y equation:


Simplifying
z = 90 + -4x + 6y

Solving
z = 90 + -4x + 6y

Solving for variable 'z'.

Move all terms containing z to the left, all other terms to the right.

Simplifying
z = 90 + -4x + 6y

See similar equations:

| 4x^2=61x+119 | | -(7-t)=21 | | z^2-64= | | x=(180-2x+3y)-(90-2x+3y) | | x=(180-2x+3y)-(190-2x+3y) | | 6(z-3)=30 | | -1.5+0.5y^2=y | | 3(y^2-2x-3)=0 | | 3(m+5)=27 | | (3y^2)-6x-9=0 | | 24+14y+y= | | -11/-5 | | 7x+3y=3.58 | | 5(f+2)=20 | | 2+(-6)+3= | | (y^2)dy+(2xy^3-6x)dx=0 | | 7(b-1)=14 | | 37x-28-37x=37x-28-37x | | 5log(4x+1)=7 | | 6-(7)+3= | | 2.9+5=4.7w-7.6 | | (-2xy^2)*(3x^3y)= | | 2(5x-4)=2(19x+12) | | 90=(2-w)(5+w) | | 6xy^2*4xy= | | x^3=360 | | y^2-6xy+5x^2=0 | | f(x+h)=x^2-8x | | 0.99+27=42.72 | | f(x+5)=x^2-8x | | 2x^3+15x^2-8x-60=0 | | 0.99+17=42.72 |

Equations solver categories